Field reports, Thomas H. Kent, fall 1989 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1989)
Field reports and bird sightings for fall 1989 by Thomas H. Kent with detailed notes for some sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1989. Epson - sheet feed